The constraints led approach principles for sports coaching and practice design - Renshaw, Ian; Newcombe, Daniel (Daniel J.); Roberts, Will (William M.); Davids, K. (Keith) 1953- (Routledge studies in constraints-based methodologies in sport, 2019)
For the last 25 years, a constraints-based framework has helped to inform the way that many sport scientists seek to understand performance, learning design and the development of expertise and talent in sport. The Constraint-Led Approach: Principles for sports Coaching and Practice Design provides students and practitioners with the theoretical knowledge required to implement constraint-led approaches in their work. Seeking to bridge the divide between theory and practice, the book sets out an environment design framework, including practical tools and guidance for the application of the framework in coaching and skill acquisition settings. it includes chapters on constraint-led approaches in golf, athletics and hockey, and provides applied reading for undergraduate and postgraduate students of motor learning, skill acquisition and developing sport exercise. Providing a thorough grounding in the theory behind constraints-led approaches to skill acquisition, and a foundational cornerstone in the Routledge Studies in Constraints-Based Methodologies in Sport series, this is a vital pedagogical resource for students and practising sport coaches, physical education teachers and sport scientists alike